Pemberdayaan Kader Posyandu Tentang Praktik Pembuatan MPASI-Lokal ”Ikan Kembung Como” di Wilayah RW021 Serua-Ciputat : Indonesia - Mulyani, Erry Yudhya; Sari, Yumelda; Widiastuti, Mariyana (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Based on SSGI 2022 data, the prevalence of stunting in Indonesia is 21.6% and in the South Tangerang city area in 2023 it is 9.0%. This figure is still above the government's target. One effort that can be made is by utilizing local food to improve the nutritional status of children under five. This activity is an educational program through training in making local MPASI biscuits made from "Como Mackerel Fish". This activity involved all 12 cadres of Posyandu Kartini Manyar RW021 Serua-Ciputat. This activity is carried out for 3 months (July – September 2023). The activities take the form of socialization, cooking demonstrations, and practice in making local MPASI biscuits. Online socialization via Zoom for 60 minutes (20 minutes lecture, 40 minutes question and answer discussion). Next, demos and practices were carried out for 6 hours as well as other product modifications for approximately 2 weeks. The average length of work for cadres is more than 2 years, namely (6.8 ± 5.5 years). This activity resulted in more than 90.0% of cadres having knowledge about local MPASI and toddler nutrition. Meanwhile, the attitude of more than 85.0% of cadres is positive, understanding the importance of local MPASI and how to provide it. About 90.0% of mothers can practice making MPASI locally (at home). Therefore, it is necessary to carry out a sustainable training program that can have creative and educational, economic value regarding local MPASI made from "Como Mackerel".